Remembering the Disaster: Isra Miraj Commemoration at the Telomoyo Slope Inscription Site during COVID-19 Pandemic - Galuh Ambar Sasi; Rosiana Eva Rayanti (Institut Agama Islam Negeri Salatiga, 2022)
Isra Miraj is a commemoration of the amazing journey of the Prophet Muhammad PBUH to the seventh heaven in one night. In Indonesia, this day is celebrated by various traditions, including rejeban in Java. Some activities such as bersih desa (cleaning the village) ceremony, eating together in haunted or ancestral burial places, and performing various artistic performances are held in rejeban. By applying oral tradition methodology suggested by Jan Vansina (1964), this paper aims to propose that rejeban on the Telomoyo slope is more than a commemoration of Isra Miraj resulted from Islamic-Javanese acculturation. This tradition is a medium inheriting the collective memory of natural disasters in the XIX century. In the context of the Covid-19 pandemic, rejeban is a reminder of local disasters occurred globally.